Učinkovitost uporabe navidezne resničnosti pri terapiji kronične bolečine v vratu - Sergaš, Blaž (Rehabilitacija (Ljubljana), 2024)
Background: Neck pain is a major physical, psychological and socioeconomic problem in modern society, and its prevalence is influenced by several factors. Virtual reality (VR) therapy is expected to reduce the intensity of pain present in acute pain syndromes, especially during therapy, but the effectiveness of VR therapy in chronic pain syndromes is poorly understood due to the relatively new technology and the complexity of the phenomenon of chronic pain syndromes. Methods: PubMed, Scopus and PEDro databases were used for literature search. In the literature review, we performed a content analysis of the findings of the included studies. Results: Five studies published between 2018 and 2022 were included in the literature review. The samples in the studies covered the age group where chronic neck pain occurs most frequently. Four studies found VR therapy to be more effective than conventional physiotherapy treatment, and one study found the same effect of the two. Conclusions: VR therapy in the management of chronic neck pain is indicated as an effective stand-alone or adjunctive therapy, especially for reducing pain intensity, kinesiophobia and patients’ level of handicap. The effective ness of VR therapy is attributed to its motivational and interactivity effect, which contributes to a positive distraction from pain.
Keywords: cervical spine; Cervical Vertebrae; Chronic Pain; fizioterapija; kronična bolečina; navidezna resničnost; physical therapy; rehabilitation; sensorimotor training; senzomotorična vadba; Virtual Reality; vratna hrbtenica